Multiparticulate Systems of Ezetimibe Micellar System and Atorvastatin Solid Dispersion Efficacy of Low-Dose Ezetimibe/Atorvastatin on High-Fat Diet-Induced Hyperlipidemia and Hepatic Steatosis in Diabetic Rats - Carlos Torrado-Salmerón (Pharmaceutics, 2021)
The aim of this study was to develop multiparticulate systems with a combination of ezetimibe micellar systems and atorvastatin solid dispersions using croscarmellose as a hydrophilic vehicle and Kolliphor RH40 as a surfactant. The presence of a surfactant with low hydrophilic polymer ratios produces the rapid dissolution of ezetimibe through a drug–polymer interaction that reduces its crystallinity. The solid dispersion of atorvastatin with low proportions of croscarmellose showed drug–polymer interactions sufficient to produce the fast dissolution of atorvastatin. Efficacy studies were performed in diabetic Goto-Kakizaki rats with induced hyperlipidemia. The administration of multiparticulate systems of ezetimibe and atorvastatin at low (2 and 6.7 mg/kg) and high (3 and 10 mg/kg) doses showed similar improvements in levels of cholesterol, triglycerides, lipoproteins, alanine transaminase, and aspartate transaminase compared to the high-fat diet group. Multiparticulate systems at low doses (2 and 6.7 mg/kg of ezetimibe and atorvastatin) had a similar improvement in hepatic steatosis compared to the administration of ezetimibe and atorvastatin raw materials at high doses (3 and 10 mg/kg). These results confirm the effectiveness of solid dispersions with low doses of ezetimibe and atorvastatin to reduce high lipid levels and hepatic steatosis in diabetic rats fed a high-fat diet.